Religion and Diplomacy: The Dynamics of Indonesian-Afghanistan Relations During President Joko Widodo Government - Fatimatuzzahro Fatimatuzzahro; Gonda Yumitro (Al-Albab, 2022)
This study aims to analyze the dynamics of relations between Indonesia and Afghanistan during the reign of Joko Widodo before and after the Afghan coup by the transnational Islamic movement of the Taliban. Even though the Taliban is back in power in Afghanistan, relations between Indonesia and the Afghan government are still going well. This research is a qualitative descriptive study using the concept of multitrack diplomacy to answer the problem of this research. The method to collect data by literature study, the journals used as references are reputable journals randomly obtained from several publishers such as Taylor Francis Online and Sage. In addition, researchers also use Harzing publish or Perish. When searching for articles, the primary key used by the authors in Harzing is Indonesia Afghanistan, Indonesia-Afghanistan relations, Jokowi Afghanistan, Indonesia’s response to Afghanistan. The authors also used an open knowledge map from 2014-to 2021 to complete the data source. The authors imported the article into Mendeley in the next stage and then used Vosviewer software to determine clusters and research gaps. The authors found that Indonesia and Afghanistan have an excellent relationship, as seen by the contribution of Indonesia, which is actively involved in responding to Afghanistan’s internal conflict with the Taliban in efforts to handle Afghan refugees and the involvement of non-governmental organizations. The was also a shift in the focus of issues in Indonesia’s relations with Afghanistan. Before the Taliban coup in Afghanistan, the Indonesian government was more focused on the topic of refugees.